A weather forecast-based control for the improvement of PCM enhanced radiant floors. (April 2022) - Cesari, Silvia; Emmi, Giuseppe; Bottarelli, Michele
Highlights: Radiant floor system enhanced with PCM was investigated. A weather forecast-based control strategy was implemented in TRNSYS. Outdoor air temperature and sky conditions (clear/cloudy) were used as parameters. Two prediction horizons, 12-h and 6-h time frame, were considered. Energy savings of 4% and 8% on heating and on cooling energy demand were estimated. Abstract: Significant energy savings and thermal comfort improvement related to radiant floor systems may not be achieved when underfloor heating/cooling is adopted in lightweight building envelopes. Phase change materials (PCMs) are suitable candidates for providing the necessary thermal inertia with a minimum effect on the construction technology. Impacting variables like internal heat gains, weather conditions and dynamic energy price require the adoption of advanced control strategies to ensure and maximise the energy benefits of PCMs. Despite the potential of model predictive control using weather prediction data has been widely examined by the literature, there is a lack of studies experimentally analysing their implementation in PCM enhanced radiant floor systems. Within the H2020 European project IDEAS the integration of PCMs in a radiant floor system was examined by the University of Ferrara through numerical and experimental investigation. A first prototype was then installed in a small experimental building characterised by a low thermal capacity. Analysis of the monitoring data for the heating period showed that solar radiation strongly impacts on the lightweight building envelope in a short time. Without suitable control, the contribution of PCM that slowly reduced its heat flux during its transition, together with solar heat gains, resulted in an excessive increase in indoor air temperature, wasting the PCM energy saving potential. The aim of the study is the evaluation of a control strategy to improve the management of PCM enhanced radiant floor systems in relation to forthcoming weather conditions in lightweight buildings. The control routine was implemented in the corresponding dynamic energy model in TRNSYS. Results estimated achievable energy saving equal to about 4% and 8% on the heating and the cooling energy demand respectively.